APLIKASI MOBILE STUDENT ASSISTANT PRODI SISTEM INFORMASI DI STMIK INDONESIA PADANG BERBASIS ANDROID - Amuharnis Chaniago (Lambung Mangkurat University, 2019)
Mobile learning (m- learning) is a learning model that utilizes information and communication technology, bring the benefits of the availability of teaching materials that can be accessed at any time in the form of text, image, or video content. Almost all the material presented for lectures in major of information system in STMIK Indonesia in the form of M-learning content. This causes, need for an application that can facilitate to share M-learning either that teaching materials given lectures and tasks that have been completed by Student. This application mobile developed based on Android with mobile java programming language and Firebase as database. System development for this research is System Development Life Cycle (SDLC) with waterfall approach. The result of this researches is the creation of a Mobile Student Assistant Application based on Android that can be used to share m-learning, uploading, and downloading lectures by dean and students in major of information system in STMIK Indonesia Padang.Keywords: Mobile Student Asistant, AndroidMobile learning (m-learning) merupakan model pembelajaran yang memanfaatkan teknologi informasi dan komunikasi, membawa manfaat ketersediaan materi ajar yang dapat diakses setiap saat berupa konten teks, gambar, maupun video. Hampir seluruh materi yang disajikan untuk perkuliahan di jurusan sistem informasi pada STMIK Indonesia berupa konten m-learning. Hal ini menyebabkan dibutuhkannya sebuah aplikasi yang dapat memudahkan untuk berbagi m-learning baik itu materi ajar yang diberikan dosen maupun tugas yang telah diselesaikan mahasiswa. Aplikasi Mobile Student Assistant ini dikembangkan berbasis Android dengan bahasa pemrograman Java mobile dan Firebase sebagai basis data. Metode pengembangan sistem untuk peneitian ini adalah System Development Life Cycle (SDLC) dengan pendekatan Waterfall. Hasil akhir dari penelitian ini adalah terciptanya Aplikasi Mobile Student Assistant berbasis Android yang dapat digunakan untuk berbagi m-learning, mengupload, dan download tugas perkuliahan oleh mahasiswa program studi Sistem Informasi pada STMIK Indonesia Padang.Kata kunci: Android, Mobile Learning